2018
DOI: 10.1016/j.stemcr.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

FGF2 Induces Migration of Human Bone Marrow Stromal Cells by Increasing Core Fucosylations on N-Glycans of Integrins

Abstract: SummarySince hundreds of clinical trials are investigating the use of multipotent stromal cells (MSCs) for therapeutic purposes, effective delivery of the cells to target tissues is critical. We have found an unexplored mechanism, by which basic fibroblast growth factor (FGF2) induces expression of fucosyltransferase 8 (FUT8) to increase core fucosylations of N-linked glycans of membrane-associated proteins, including several integrin subunits. Gain- and loss-of-function experiments show that FUT8 is both nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…It has previously been reported that in MSCs treated with FGF‐2 in 2D, FGF‐2 treatment upregulates genes associated with cell proliferation and downregulates genes associated with collagen‐related processes in MSCs. [ 14 ] Among the 20 most overrepresented GO terms associated with MSCs treated with FGF‐2 here, we found many terms related to mitosis and cell division, clearly showing the proliferative effect of FGF‐2 (Figure 4b). On the other hand, GO terms that were overrepresented in the absence of FGF‐2 almost all relate to the ECM (Figure 4c).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…It has previously been reported that in MSCs treated with FGF‐2 in 2D, FGF‐2 treatment upregulates genes associated with cell proliferation and downregulates genes associated with collagen‐related processes in MSCs. [ 14 ] Among the 20 most overrepresented GO terms associated with MSCs treated with FGF‐2 here, we found many terms related to mitosis and cell division, clearly showing the proliferative effect of FGF‐2 (Figure 4b). On the other hand, GO terms that were overrepresented in the absence of FGF‐2 almost all relate to the ECM (Figure 4c).…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, GO terms that were overrepresented in the absence of FGF‐2 almost all relate to the ECM (Figure 4c). We compared our dataset representing 3D‐cultured MSCs to the published RNAseq dataset of MSCs treated with FGF‐2 in 2D, [ 14 ] and found a positive correlation between both datasets (Figure S5a, Supporting Information). However, 3D culture induced larger gene expression changes than when MSCs were cultured in 2D, which were mainly related to cell proliferation (induced by FGF‐2) and ECM (reduced by FGF‐2) GO terms (Figure S5b,c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During bone remodeling and fractured-bone regeneration, MSCs migrate to the bone surface or fracture site and then differentiate into OBs to reconstruct the bone [76], subsequent to the osteoclastic resorptive phase. It has been well demonstrated that local growth factors and signals play important roles in the recruitment and commitment of MSCs [77], such as the bone morphogenetic protein (BMP) family [78], insulin-like growth factor (IGF) [79,80], TGF-β [68,81], fibroblast growth factor 2 (FGF-2) [82], vascular endothelial growth factors (VEGF) [78], and platelet-derived growth factors (PDGFs) [83,84]. Moreover, emerging evidence showed that many of these local factors are associated with the viability and activity of OCs [17,20,54].…”
Section: Effect Of Osteoclasts On Mesenchymal Stem Cell Recruitment Amentioning
confidence: 99%
“…The two short-term samples also shared common transcripts, including Irgm2, Igtp, D8Ertd82e, Bcl3, and Serpina3f, which were further elevated compared to their corresponding controls. Most of these common genes participate in immune and complement pathways [18][19][20] .…”
Section: Resultsmentioning
confidence: 99%